Oracle Incident Response and Forensics Preparing for and Responding to Data Breaches - Finnigan, Pete (Apress, 2018)
Take the right steps when a breach of your Oracle Database environment becomes known or suspected. You will learn techniques for discerning how an attacker got in, what data they saw, and what else they might have done. This book helps you understand forensics in relation to Oracle Database, and the tools and techniques that should be used to investigate a database breach. You will learn the measures to put in place now to make it harder for an attack to be successful, and to aid in the detection and investigation of future attacks. You will know how to bring together tools and methods to create a holistic approach and investigation when an event occurs, helping you to be confident of your ability to react correctly and responsibly to threats against your organization's data. What You'll Learn: Detect when breaches have or may have occurred React with confidence using an organized plan Determine whether a suspected breach is real Determine the scope of data that has been compromised Preserve evidence for possible criminal prosecutions Put in place measures to aid future investigations.